CHARACTER EDUCATION VALUE IN FERDINAND MOVIE DIRECTED BY CARLOS SALDANHA - Mufidah, Evi Zahrotul; Wulandari, Rifa Suci; Ro'is, Syamsuddin (Jurnal Bahasa dan Sastra, 2022)
Education is a system that regularly carries a wide mission that is not only about the delivery of knowledge to learners but wider. Education must be able to build a good character of every learner. Therefore, it is necessary to cultivate the values of character education to the learners. There are 18 values in Indonesian character education idea formulated by Education Ministry. In practice, integrating the 18 values can be done through various ways, such as utilizing learning media which is claimed more effective, such as using movie. The purpose of this research is to find the values contained in the Ferdinand movie and also to know which values are most highlighted. This research is descriptive qualitative. The writer uses documentation as a technique of collecting the data. The data collection which relates to research conducted through internet searching, and library research. The analysis data technique used in this study is descriptive analysis. The result of this research is there are 9 values contained in Ferdinand movie; they are honest, hard working, creative, appreciating achievement, friendly, love peace, environmental care, sociality and responsibility. The most highlighted value in Ferdinand movie is sociality. Movie can be used as a medium in learning activities as well as a media to instill the values of character education in every student.